Therapeutic Potential of Invariant Natural Killer T Cells in Autoimmunity - Van Kaer, Luc; Wu, Lan (Frontiers in Immunology, 2018)
Tolerance against self-antigens is regulated by a variety of cell types with immunoregulatory properties, such as CD1d-restricted invariant natural killer T (iNKT) cells. In many experimental models of autoimmunity, iNKT cells promote self-tolerance and protect against autoimmunity. These findings are supported by studies with patients suffering from autoimmune diseases. Based on these studies, the therapeutic potential of iNKT cells in autoimmunity has been explored. Many of these studies have been performed with the potent iNKT cell agonist KRN7000 or its structural variants. These findings have generated promising results in several autoimmune diseases, although mechanisms by which iNKT cells modulate autoimmunity remain incompletely understood. Here we will review these preclinical studies and discuss the prospects for translating their findings to patients suffering from autoimmune diseases.